DEMOGRAPHIC PROFILE OF CATARACT PATIENTS ATTENDING TERTIARY CARE EYE HOSPITAL – A CLINICAL STUDY - Rao, Attada Tarakeswara; Santhosha Nikhila, Reddi; Manasa, Challakonda Lalitha (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of the study was to review demographic characteristics and comorbid systemic disorders in cataract patients attending tertiary care eye hospital. Methods: A hospital-based and prospective study was conducted on 2024 cataract patients attending tertiary care eye hospital from January 2022 to August 2022. All patients were subjected to detailed history taking and ocular examination. Age, gender, and comorbid systemic diseases were recorded. Results: A total of 2024 patients were included in the study. Of which 1226 (60.5%) were females while 798 (39.5%) were males. Seven hundred and forty-nine patients (37%) were found to be between 51 and 60 years of age followed by 589 patients (29.1%) were found between 61 and 70 years. Among 2024 patients with cataracts, 687 (33.9%) were found to have comorbidities. About 64.6% were females and 35.4% were males among the patients with comorbidities. Hypertension was the most common systemic comorbidity (371 patients-54%) followed by diabetes mellitus (200 patients – 29.1%). Conclusion: An increasing prevalence of non-communicable diseases necessitates a thorough screening before cataract surgery to ensure fitness of the patients for cataract surgery. The presence of systemic comorbidity increase the number of investigations needed for fitness of the patient for cataract surgery, also it can cause intra operative complication and may affect surgical outcome. This suggests that debilitating comorbidities also play a role in patients not getting their cataracts operated timely as they are engrossed with more life-threatening issues. Ophthalmologist has to identify the coexisting systemic diseases and they should be adequately controlled before surgery to avoid intraoperative and post-operative complications and to achieve better quality of life for patients.